2016
DOI: 10.1108/caer-09-2014-0086
|View full text |Cite
|
Sign up to set email alerts
|

Off-farm employments and land rental behavior: evidence from rural China

Abstract: Purpose – The purpose of this paper is to examine the impacts of off-farm labor employments on household land rental behavior in rural China. Design/methodology/approach – IV-Probit and IV-Tobit model are used to identify the estimate of interest. Findings – The results indicate that households with more members participating in either migration or local off-farm work are more/les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 26 publications
5
63
0
Order By: Relevance
“…Considering the sample ranged from 2003 to 2013, the year dummies are also included in the model, to capture the unobservable year-specific effects. In practice, the Huber-White robust estimator of variance is calculated for appropriate inference [35].…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Considering the sample ranged from 2003 to 2013, the year dummies are also included in the model, to capture the unobservable year-specific effects. In practice, the Huber-White robust estimator of variance is calculated for appropriate inference [35].…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Some studies found that off-farm employment and migration had critical positive impacts on farmland renting-out behavior of rural households [22,26,27]. Not only did availability of off-farm employment significantly improve farmland rental, but tenure security and agricultural ability also played a critical role in farmland rental [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Both forestland transfer and off-farm work are determined jointly in households' decision-making process. The simultaneous causality leads to an endogeneity of off-farm employment, which can bias the estimation results [16,19,[27][28][29]. Meanwhile, the fact that most of the sample households choose not to transfer their forestland implies that the dependent variable is censored.…”
Section: Model Specificationmentioning
confidence: 99%
“…Endogeneity is a theoretically justified assumption as the land transfer and off-farm employment must be simultaneously determined in households' decision-making [27]. This assumption has also gained empirical evidences [16,19,28,29] (For instance, Feng and Heerink [28] and Liu et al [29] have found that households' land transfer decisions and off-farm employment decisions are closely interrelated. However, their studies focus on the context of farmland transfer with the data from specific regions, while this paper employs nationally representative data to investigate the behavior of forestland transfer).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation